Investigating Children as Gatekeepers to Tactical Athlete Nutrition - J. Joyce; A. Sampson; P. Gonzalez Sanchez; B. Tuttle (Journal of the Academy of Nutrition and Dietetics, 2024)

Investigation of Significant Others as Gatekeepers to Tactical Athlete Nutrition - J. Joyce; M. Green; P. Gonzalez Sanchez; B. Tuttle (Journal of the Academy of Nutrition and Dietetics, 2023)

The influence of sedimentary architecture on the formation of earthquake-induced liquefaction features: A case study in the New Madrid seismic zone - Can Güven; Lorraine W. Wolf; Martitia P. Tuttle; Stephanie R. Rogers (Engineering Geology, 2023)

Legacy Effects of Russian Olive (Elaeagnus angustifolia L.) in a Riparian Ecosystem Three Years Post-Removal - Gabrielle L. Katz; Graham M. Tuttle; Michael W. Denslow; Andrew P. Norton (Wetlands, 2020)

Avian injury assessment for the Deepwater Horizon oil spill - P. L. Tuttle; J. M. Hemming (Environmental Monitoring and Assessment, 2019)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Pelagic seabird density and vulnerability in the Gulf of Mexico to oiling from the Deepwater Horizon/MC-252 spill - J. C. Haney; J. M. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
Using ship-based surveys, the Natural Resource Damage Assessment (NRDA) Trustees assessed the external oiling of offshore and pelagic marine birds inhabiting the northern Gulf of Mexico (Gulf) in the year following the Deepwater Horizon oil spill (DWH spill). Study objectives were to (1) collect data on pelagic seabirds that were visibly oiled, (2) collect data to estimate abundance of seabirds in offshore and pelagic waters, and 3) document the location and condition of any bird carcasses encountered. Methods employed included strip line transects and station point counts. Surveys were conducted within a study area bound by the Texas-Mexico border and the Dry Tortugas of Florida to the south, and the nearshore coastal waters of the northern Gulf of Mexico. A total of 5665 strip line transects and 386 station point-counts of variable duration were collected during the study. More than 23,000 individual seabirds comprising 45 estuarine, coastal, offshore, and pelagic species were tallied. Average daily abundance of seabirds detected varied from a low of approximately 7 birds/day in November 2010 along regions of the mid- and outer continental shelf to a high of more than 580 birds/day in June 2011 within the near-shore, coastal waters of the northern Gulf.

Persistence of Viruses by qPCR Downstream of Three Effluent-Dominated Rivers in the Western United States - Hannah P. Sassi; Koiya D. Tuttle; Walter Q. Betancourt; Masaaki Kitajima; Charles P. Gerba (Food and Environmental Virology, 2018)

Assessment of metal contamination in the biota of four rivers experiencing varying degrees of human impact - Gretchen K. Bielmyer-Fraser; Matthew Neal Waters; Christina G. Duckworth; Pratik P. Patel; Benjamin Cole Webster; Amber Blocker; Cliff Hunter Crummey; Aundrea Nicole Duncan; Somuayiro Nadia Nwokike; Codie Richard Picariello; James T. Ragan; Erika L. Schumacher; et al. (Environmental Monitoring and Assessment, 2017)

Patterns, causes and consequences of defensive microbiome dynamics across multiple scales - Andrew H. Smith; Piotr Łukasik; Michael P. O'Connor; Amanda Lee; Garrett Mayo; Milton T. Drott; Steven Doll; Robert Tuttle; Rachael A. Disciullo; Andrea Messina; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2015)
The microbiome can significantly impact host phenotypes and serve as an additional source of heritable genetic variation. While patterns across eukaryotes are consistent with a role for symbiotic microbes in host macroevolution, few studies have examined symbiont‐driven host evolution or the ecological implications of a dynamic microbiome across temporal, spatial or ecological scales. The pea aphid, Acyrthosiphon pisum , and its eight heritable bacterial endosymbionts have served as a model for studies on symbiosis and its potential contributions to host ecology and evolution. But we know little about the natural dynamics or ecological impacts of the heritable microbiome of this cosmopolitan insect pest. Here we report seasonal shifts in the frequencies of heritable defensive bacteria from natural pea aphid populations across two host races and geographic regions. Microbiome dynamics were consistent with symbiont responses to host‐level selection and findings from one population suggested symbiont‐driven adaptation to seasonally changing parasitoid pressures. Conversely, symbiont levels were negatively correlated with enemy‐driven mortality when measured across host races, suggesting important ecological impacts of host race microbiome divergence. Rapid drops in symbiont frequencies following seasonal peaks suggest microbiome instability in several populations, with potentially large costs of ‘superinfection’ under certain environmental conditions. In summary, the realization of several laboratory‐derived, a priori expectations suggests important natural impacts of defensive symbionts in host‐enemy eco‐evolutionary feedbacks. Yet negative findings and unanticipated correlations suggest complexities within this system may limit or obscure symbiont‐driven contemporary evolution, a finding of broad significance given the widespread nature of defensive microbes across plants and animals.

Ecological Sustainability as the Fourth Landmark in the Development of Conservation Ethics - PETER S. WHITE; JULIE P. TUTTLE (Conservation Biology, 2013)
Aldo Leopold, in “The Land Ethic,” made 2 important contributions to conservation ethics: he emphasized the community and ecosystem levels of organization and he explicitly included people as members of the biotic community. Leopold's writings remain eloquent, inspirational, and influential, but the ideas he describes are inherently complex, and ecological science has continued to evolve since “The Land Ethic” was published in 1949. We used 4 sets of quotations from Leopold's essays to develop our commentary on the meaning of and challenges in interpreting his work and to explore the ongoing development of conservation ethics: the “A‐B cleavage” (Leopold's description of the contrast between utilitarian value versus a broader definition of value in nature), “land health” and the rightness of human action, the right of all species to continued existence in natural populations “at least in spots,” and humans as “plain member[s] and citizen[s]” of the “land‐community.” We define the broader function of land and land health in “The Land Ethic” as including completeness, dynamic stability, and self‐renewal in a way that incorporates the needs of humans and all other species. We argue that the consequences of implementing Leopold's land ethic include multiple conservation goals nested within an overall systems approach and that conservation science must clarify the implications of Leopold's ethic by quantitatively investigating and defining large‐scale, system‐level ecological sustainability. At this scale, land use will encompass areas ranging from large expanses of wilderness to areas dominated by humans. La Sustentabilidad Ecológica como el Cuarto Hito en el Desarrollo de la Ética de la Conservación

Geomorphic and stratigraphic evidence for an unusual tsunami or storm a few centuries ago at Anegada, British Virgin Islands - Brian F. Atwater; Uri S. ten Brink; Mark Buckley; Robert S. Halley; Bruce E. Jaffe; Alberto M. López-Venegas; Eduard G. Reinhardt; Maritia P. Tuttle; Steve Watt; Yong Wei (Natural Hazards, 2012)

Three cases of gastric prolapse through the gill slit in sand tiger sharks, Carcharhinus taurus (Rafinesque) - A D Tuttle; O Burrus; M A Burkart; P W Scott; M K Stoskopf; C A Harms (Journal of Fish Diseases, 2008)

The use of liquefaction features in paleoseismology: Lessons learned in the New Madrid seismic zone, central United States - Martitia P. Tuttle (Journal of Seismology, 2001)